2017
DOI: 10.1177/1479972317709643
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health care professional perspectives on using telehealth to deliver pulmonary rehabilitation

Abstract: The objective of this study was to identify the necessary features of pulmonary telerehabilitation (P-TR) from the perspectives of individuals living with chronic lung disease and health care professionals (HCPs) who deliver pulmonary rehabilitation (PR). Focus groups were carried out with patients (n = 26) and HCPs (n = 26) to elicit and explore their opinions about the critical elements of in-person PR and ideas for how these elements could be supported using technology. A questionnaire was used to assess te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…First, several studies found that health professionals reported technical tasks as a great barrier to their job and professional role. 20 , 26 , 44 47 Similarly, the participants in this study experienced that technical tasks increased their preexisting work burden and undermined their professional identity. Second, more studies emphasized that telecare would not be able to replace the physical meeting because important communication would be missed.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…First, several studies found that health professionals reported technical tasks as a great barrier to their job and professional role. 20 , 26 , 44 47 Similarly, the participants in this study experienced that technical tasks increased their preexisting work burden and undermined their professional identity. Second, more studies emphasized that telecare would not be able to replace the physical meeting because important communication would be missed.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, a study by Inskip et al found that health professionals reported that being able to support patients who otherwise would not participate in rehabilitation was satisfying and made their job meaningful. 47 Likewise, we found that making a difference to the patients was an often mentioned motivator to perform TR.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Another potential strategy for increasing access to PR in rural areas is to explore the use of telehealth technologies, which have been successfully used in other countries, including Scotland and Canada, for remote delivery of PR services. [24][25][26] Expansion of PR services to underserved areas is an important first step in improving access. However, the availability of a PR program in a geographic area does not guarantee that all patients in need of the service will be able to obtain it or that the services provided are high quality.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the educational videos and instruction manuals in an e-consultation platform should be elaborately prepared and the real-time supervision is recommended to support patient conduct of tele-PR in an effective and safe way [202]. To promote physical exercise as an example, patients with mild to moderate symptoms can, for example, use posture and movement monitoring technologies, such as depth-cameras or wearable systems [203][204][205]. With remote feedback on the monitored information from the patients, training effectiveness can be ensured with improved motivation, which can potentially relieve stress and anxiety.…”
Section: Tele-rehabilitationmentioning
confidence: 99%